The Influence of Using Chain Story activity on Procedural Text towards Students’ Speaking Skill - Iponiasih Iponiasih (Journal of English Education Studies, 2018)
This research aims to find out the influence of using chain story activity on procedural text towards students’ speaking skill. The researcher employs quantitative research with the method of experiment. She uses quasi experimental design in the type of non-equivalent control group to get the sample. The population are 157 students of the second grade students of Madrasah Aliyah Mathla’ul Anwar Pusat Menes. The samples are 26 students of the XI IPA 2 as the experimental class which is treated by using chain story activity and 24 students of XI IPA Tahfidz as the control class which is treated without using chain story activity. The data is collected by using oral test. The test are divided into two, pre-test and post-test. After the process of collecting the data finished, the researcher analizes them by using statistical computation. Based on the research findings after calculating the data, the result shows that there is significant influence of using chain story activity on procedural text towards students’ speaking skill.